POLITICAL COMMUNICATION:: Instagram Rembuk Pemuda and Voter Participation Issues among Gen Z (E-Journal of Cultural Studies, 2026)
This study investigates the role of Rembuk Pemuda on Instagram as a virtual public sphere that addresses the persistent issue of low voter participation among Generation Z in Denpasar. Using a qualitative descriptive approach, data were collected through digital observations, document analysis, and in-depth interviews (WWC) with community leaders, content creators, and Gen Z followers across Denpasar Barat, Denpasar Timur, Denpasar Utara, and Denpasar Selatan. The findings reveal that Rembuk Pemuda effectively utilizes visual storytelling, interactive content, and data-driven messages to enhance political literacy and civic engagement among youth. Informants emphasized that the platform’s neutral stance, relatable tone, and credible information foster trust and encourage reflective discussion. Through infographics, short videos, and participatory comment spaces, Rembuk Pemuda transforms abstract political issues into accessible, culturally resonant narratives. Analysis using Habermas’s Theory of Communicative Action shows that the platform fulfills the principles of clarity, truth, sincerity, and appropriateness, enabling rational-critical dialogue within digital environments. However, challenges such as algorithmic bias, gender dynamics, and awareness fatigue persist. Despite these constraints, the study demonstrates that youth-led civic communities like Rembuk Pemuda can reshape digital communication into participatory and inclusive spaces that promote democratic awareness. The findings contribute to a deeper understanding of how communicative action and digital rhetoric operate in Indonesia’s emerging digital democracy.Keywords: Political Communication, Instagram, Digital Public Sphere, Generation Z, Rembuk Pemuda